Market research in practice : how to get greater insight from your market - Hague, Paul N.; Hague, Nick, 1974-; Morgan, Carol-Ann, 1958- (Market research in practice, 2013)
" Lively and accessible, Market Research in Practice is a practical introduction to market research tools, approaches and issues. Offering a clear, step-by-step guide to the whole process - from planning and executing a project through to analysis and presentation of the findings, the book explains how to use tools and methods effectively and obtain the most reliable results. With new chapters on using market research, international aspects and new research trends (including coverage of social media research and mobile surveys) this fully updated second edition also includes the latest information on carrying out market research design, secondary research, sampling and statistics, questionnaire design, data analysis and reporting.Accompanied by a range of online tools and templates and supported throughout by examples from real market research practice, this is a valuable guide for students, researchers, marketers and users of market research"--Resumé vydavatele